Pengaruh Promosi Penjualan dan Lokasi Produk Terhadap Kepuasan Konsumen Pada Produk Chicken Nugget So Good Food Di Transmart Gatot Subroto Medan - Irvan Rolyesh Situmorang; Aminuddin Aminuddin (JEKKP (Jurnal Ekonomi, Keuangan dan Kebijakan Publik), 2022)
The purpose of this study was to determine the effect of promotion on consumer satisfaction with Chicken Nugget So Good Food at Transmart Gatot Subroto Medan, the effect of product location on consumer satisfaction with Chicken Nugget So Good Food at Transmart Gatot Subroto Medan, the effect of promotion and location on consumer satisfaction at Chicken Nugget So Good Food products at Transmart Gatot Subroto Medan. The population in this study at Transmart Gatot Subroto Medan was 6531 customers and the samples used were 44 customers, while the determination technique used Incidental Sampling. The data sources in this study are primary data, namely data obtained directly from the research location and secondary data, namely data derived from reports, books and journals related to it. Data collection techniques are observation, interviews, and questionnaires. The data analysis technique used is multiple linear regression analysis. The results of multiple regression analysis are Y = 4.243+ 0.540X1 + 0.265X2 + e which shows promotion and location have a positive and significant effect on customer satisfaction. The results of the partial test (t) show that promotion has a positive and significant effect on customer satisfaction where it can be seen that the tcount value is 6.072 ttable 1.682 and the location variable also has a positive and significant effect on customer satisfaction where it can be seen that the tcount value is 3.135 ttable 1.682. The result of the coefficient of determination is 0.622, this shows that 62.2% of the Consumer Satisfaction variable is influenced by promotion and location, in other words, promotion and location affect customer satisfaction by 62.2%, while the remaining 37.8% is influenced by other than this research